2009
DOI: 10.1016/j.ydbio.2009.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial cells are a distinct endothelial lineage derived from Flk1+ multipotent cardiovascular progenitors

Abstract: Identification of multipotent cardiac progenitors has provided important insights into the mechanisms of myocardial lineage specification, yet has done little to clarify the origin of the endocardium. Despite its essential role in heart development, characterization of the endocardial lineage has been limited by the lack of specific markers of this early vascular subpopulation. To distinguish endocardium from other vasculature, we generated an NFATc1-nuc-LacZ BAC transgenic mouse line capable of labeling this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 58 publications
6
117
0
Order By: Relevance
“…Previous analysis of nfatc1 promoter identified a conserved region that contains binding sites for SMAD, which is a known BMP signal transducer (Zhou et al, 2005). BMP has been also implicated in endocardial differentiation in vitro, and in endocardial proliferation during the endocardial ballooning in zebrafish embryos (Misfeldt et al, 2009;Dietrich et al, 2014). However, a BMP requirement for early endocardial differentiation in vivo has not been established.…”
Section: Genetic Ablation Of the Myocardium Results In The Loss Of Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis of nfatc1 promoter identified a conserved region that contains binding sites for SMAD, which is a known BMP signal transducer (Zhou et al, 2005). BMP has been also implicated in endocardial differentiation in vitro, and in endocardial proliferation during the endocardial ballooning in zebrafish embryos (Misfeldt et al, 2009;Dietrich et al, 2014). However, a BMP requirement for early endocardial differentiation in vivo has not been established.…”
Section: Genetic Ablation Of the Myocardium Results In The Loss Of Enmentioning
confidence: 99%
“…Endocardial cells and vascular endothelial cells of blood vessels express many of the same molecular markers, which suggests a common origin of both cell types. Indeed, recent evidence argues that endocardial cells are derived from vascular endothelial progenitors (Misfeldt et al, 2009;Milgrom-Hoffman et al, 2011). However, endocardial cells exhibit distinct migratory behavior and express specialized markers such as nfatc1 (de la Pompa et al, 1998), which shows that the endocardial and vascular endothelial cells of blood vessels are biochemically distinct.…”
Section: Introductionmentioning
confidence: 99%
“…1GЈ,GЉ). These EYFP + cells are presumably endocardial progenitors (Misfeldt et al, 2009). By contrast, EYFP + cells either weakly expressed or did not express Nkx2-5 (Fig.…”
Section: Expression Analysis Of the Er71-eyfp Reportermentioning
confidence: 90%
“…Although endocardial and endothelial cells share substantial molecular and functional characteristics, a recent study demonstrated molecular and lineage distinctions between these two cell types and suggested that the endocardium and myocardium derive from a common precursor, distinct from endothelial cells (Misfeldt et al, 2009). These previous in vitro studies, and lineage studies of SHF progenitors in mice (Cai et al, 2003;Moretti et al, 2006;Verzi et al, 2005), have given rise to the idea that the endocardium derives from multipotent progenitors within the first and second heart fields (Harris and Black, 2010;Vincent and Buckingham, 2010).…”
Section: Introductionmentioning
confidence: 99%